Associations between vitamin A and K intake and lung function in the general US population: evidence from NHANES 2007–2012 - Chen, Yi-Chuan; Hung, Ming-Szu (Frontiers in Nutrition, 2024)
Introduction While nutrition's critical role in enhancing respiratory health is acknowledged, the specific impacts of vitamins A and K on lung function remain largely unexplored. The study aimed to evaluate the relationships between vitamins A and K intake and lung function. Methods The cross-sectional study focused on adults aged 20–79 with utilizing data from US National Health and Nutrition Examination Survey (NHANES) 2007–2012. Lung function was assessed by measuring forced expiratory volume (FEV1), forced vital capacity (FVC), and the ratio of these two values (FEV1/FVC). Regression model was performed to determine the associations between intake of vitamins A and K and outcomes. Results Data of 10,034 participants (representing 142,965,892 adults in the US) were analyzed. After adjusting for relevant confounders, multivariable analysis revealed 1 μg/day increase of vitamin A intake was significantly associated with 0.03 ml increased FEV1 (p = 0.004) and 0.04 ml increased forced vital capacity (FVC) (p < 0.001). In addition, 1 μg/day increase in vitamin K intake was significantly associated with 0.11 ml increased FEV1 (p = 0.022). Neither vitamin A and K intake was associated with FEV1/FVC or presence of airway obstruction. Conclusions In relatively healthy population of the US, greater vitamin A or K intake was independently associated with better lung function assessed by spirometry. Benefits of such vitamins for pulmonary health should be confirmed in future randomized controlled trials.